Hepatitis B virus: molecular genotypes and HBeAg serological status among HBV-infected patients in the southeast of Brazil - Gonçales Fernando L; Feltrin Adriana; Gonçales Eduardo SL; Vigani Aline G; Fais Viviane C; Gonçales Neiva SL; Tonetto Priscila A (BMC Infectious Diseases, 2009)
Abstract Background Knowledge of HBV genotype is very important for clinical treatment. Studies have suggested possible pathogenic and therapeutic differences among HBV genotypes. The aim of this study was to determine HBV subtypes and genotypes in HBV-infected patients in our region (southeast Brazil) and to correlate results with clinical and histopathological data. Methods One hundred and thirty-nine HBsAg-positive patients were included in the study. All patients were anti-HCV and anti-HIV negative (64% male; mean age 42 ± 14.5 years; range 7-80 years; 84% Caucasian) and were followed up at the University Hospital. A method for genotyping and subtyping HBV by partial HBsAg gene sequencing with primers common to all known genotypes was used. The viral load was measured by Amplicor Monitor assay (Roche). Results HBV genotype A was the most prevalent (55%), while genotypes C, D and F were found in 3%, 38% and 4% of HBV-infected patients, respectively. Among the patients infected by genotype A, 18.3% (14/76) were African descendents and, among the patients infected by genotype D, 11.3% (6/53) were also African descendents. In the four patients infected with genotype C, 2 were Asian descendents and 2 were Caucasians. All (7) genotype F infected patients were Caucasians. Seventy percent of our HBsAg-positive patients were HBeAg negative (62% genotypes A; 26.2% D; 7.1% C and 4.7%F). The viral load of HBV-DNA was about 5 times higher in HBeAg-positive than in HBeAg-negative patients. About 40% of these patients had alanine aminotransferase of up to 1.5 times the normal level. The mean stage of fibrosis in genotype A patients (2.8) was significantly higher than the mean stage of fibrosis in genotype D patients (2.0) (P = 0.0179). Conclusion The genotypes encountered in our HBV-infected patients were apparently a consequence of the types of immigration that occurred in our region, where European and African descendents predominate. The HBeAg-negative status predominated, possibly due to the length of time of infection. The viral load in HBeAg-positive patients was higher than in HBeAg-negative individuals. The fibrosis grade in genotype A-infected patients was more advanced than genotype D-infected patients.